Role of spot weld electrode geometry on liquid metal embrittlement crack development. (January 2020) - DiGiovanni, C.; He, L.; Pistek, U.; Goodwin, F.; Biro, E.; Zhou, N.Y.
Abstract: Advanced high strength steels (AHSS) used in automotive structural components are commonly protected using zinc coatings. However, the steel/zinc system creates the potential for liquid metal embrittlement (LME) during welding. Recent studies have examined the impact of the welding electrode geometry on LME cracking severity and found there to be some effect, but did not explore the responsible mechanisms for the changes. This work shows that a radius tip electrode provides minimal cracking while a truncated cone shape showed severe LME, particularly in the shoulder region. Thermo-mechanical simulations showed the significance of the thermal contact at the outer region of the electrode/sheet interface (weld shoulder). It was observed that when the water-cooled electrode presses into the steel during the welding, causing a contact between the steel surface and the electrode sidewall, a sudden local cooling of the weld shoulder occurs. This cooling causes contraction and tensile stresses on the material surface, leading to LME. Additionally, the magnitude and location of heat transfer between the steel and electrode is controlled by the thermal contact conductance.